EFISIENSI DAN KELAYAKAN USAHATANI PADI SAWAH TADAH HUJAN KABUPATEN BARRU - Arifin, Arifin; Pata, Abdul Asis; Azisah, Azisah; Sadat, Mohammad Anwar (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Increasing rice productivity is closely related to the ability of farmers to efficiently allocate various factors of production so that they can maximize their potential in agricultural activities. Farmers are considered technically efficient when the optimal use of inputs produces maximum output. Farmers must have the right consideration in production to get the best profit. Lowland rice income levels are expected to increase if an area has a high feasibility ratio. The purpose of this study was to analyze the technical efficiency, income, and feasibility of farming rainfed lowland rice farming. This research was conducted in Coppo Village, Barru District, and Lempang Village, Tanete Riaja District, Barru Regency. The research population was 232 people and the number of samples was 50 people. Farmer samples were taken using a multi-stage cluster random sampling technique. Data collection techniques used are observation, interviews, and documentation. Data sources are primary and secondary data. The data analysis method used is the analysis of technical efficiency, income, and feasibility. The results of this study indicate that rainfed lowland rice farming in Barru Regency is technically efficient by 76%. The income of rainfed lowland rice farming in Barru Regency is Rp. 7,532,938.39/PS. Rainfed lowland rice farming in Barru Regency is feasible to be cultivated with a feasibility value of 2.30.